SISTEM INFORMASI MANAJEMEN KESISWAAN: BERBASIS KARTU RFID DALAM PENCATATAN KEHADIRAN SISWA SMA NEGERI 1 TANGERANG SELATAN - Sandroto, Annisa Nur Aiman; Mardiana, Sri (Jurnal Multidisipliner Kapalamada, 2025)
Many schools still rely on manual student attendance recording, but these often lead to issues such as delays in recording, inaccuracies in data, and a lack of adequate oversight. This study aims to examine the application of Radio Frequency Identification (RFID) technology for registering student attendance to enhance both precision an efficiency. A qualitative reseach desaign was employed,collecting data through observations, interviews, and analysis of documents. The data analysis process included steps like reducing data, presenting findings, and drawing conclusions. The results indicate that this system can automatically and promptly register student attendance. Furthermore, it minimize serrors related to attendance tracking and improves teacher supervision in the classroom. RFID technology has proven to be an effective method for upgrading attendance recording systems and promoting more efficient and transparent management in educational institutions.